Ritos de passagem entre o humano e a natureza: Sean O Faolain ( Irlanda ) e José Lins do Rego (Brasil ) - Salles, Clice Pereira (2014)
This dissertation is dedicated to the study of the myth of the chrysalis, the myth of puberty, which is set by the Rite of Passage experienced by the protagonists of the masterpieces The Trout by Sean O'Faolain and Menino de Engenho by José Lins do Rego. The main issue of this paper raises a question that conveys the passage from the being as an individual to the being as a part of a social group, which is started by the act of union between Nature and Being and Being and Sexuality. This research aims to understand the presence of a conundrum among Nature, Human and Myth by the correlations between the characters and their ritualistic experiences. Along the study of this Rite of Passage process, we believe that, in the brief moment when the characters go through transformation, a social exclusion takes place, and that fact depicts them as members of the submerged population. The short-story, which is the genre studied for this dissertation, contains all the characteristics that can be applied to both narratives.Some authors were chosen to give theoretical foundation to this deductive and comparative study: Frank O'Connor, Mordecai Marcus, Edgar Allan Poe, Van Gennep, Victor Turner, Tania Franco Carvalhal and Eduardo Coutinho, among others.In the development of the three chapters, we put up the theories and themes proposed in dialogue with the narratives of the corpora we analysed. It s also demonstrated the way how the Rite of Passage is transposed to the Iniciation Literature besides suggesting that the characters are members of the submerged population